第57次日本南極地域観測隊気象部門報告2016 - 松元, 誠; マツモト, マコト; 藤原, 宏章; フジワラ, ヒロアキ; 三戸, 洋介; サンノヘ, ヨウスケ; 槇山, 恵子; マキヤマ, ケイコ; 加藤, 裕; カトウ, ヒロシ; Matsumoto, Makoto; Fujiwara, Hiroaki; et al. (国立極地研究所, 2020)
この報告は，第 57 次日本南極地域観測隊気象部門が 2016 年 2 月 1 日~ 2017 年 1 月 31 日まで昭和基地において行った気象観測結果をまとめたものであ る.観測方法，測器等については，総合自動気象観測装置の更新を行ったほかは 第 56 次隊とほぼ同様である.越冬期間中の特記事項としては，次のものが挙げら れる. 1)総合自動気象観測装置を JMA-95 型地上気象観測装置から JMA-10 型地上気象 観測装置に更新した. 2)ブリザードの発生回数は 33 回と 1981 年~2010 年のブリザードの平均発生回 数 24.6 を上回った.ブリザードが多数発生した影響で，月最深積雪や降雪の深さ 日合計や降雪の深さ月合計が過去 10 位以内の記録を更新した月が多かった. 3)昭和基地上空の指定気圧面において，3 月から 4 月にかけては，200 hPa より 上層の気温は平年値より低かった.また，300 hPa から下層の気温は平年値より高 かった.特に 400 hPa に関しては，4 月(00 UTC)の月平均気温の高い方から第 1 位を記録した.また，30 hPa に関しては，月平均気温の低い方から第 1 位を記録 した. 4)昭和基地上空のオゾン全量は，8 月中旬から 11 月中旬までオゾンホールの目 安となる 220 m atm-cm を度々下回り，9 月 25 日に 2016 年の最小値である 148 m atm-cm を記録した. This report describes the results of meteorological observations at Syowa Station from February 1st, 2016 to January 31st, 2017, carried out by the Meteorological Observation Team of the 57th Japanese Antarctic Research Expedition (JARE-57). The observation methods, instruments, and statistical methods used by JARE-57 were almost the same as those used by the JARE-56 observation team. The special notes during JARE-57 are as follows. 1) The automatic surface weather observation system was updated from the JMA-95 type surface weather observation system to the JMA-10 type surface weather observation system. 2) There were 33 blizzards, exceeding the average number of blizzard occurrences from 1981 to 2010, 24.6. A large number of blizzards updated many the monthly records of the deepest monthly snowfall, the total depth of daily snowfall, and the total depth of monthly snowfall fell within the 10th place. 3) From March to April, the temperature above 200 hPa was lower than normal at the standard pressure levels above Syowa Station. The temperature below 300 hPa was higher than normal for the same period. Especially, the highest monthly average temperature at 400 hPa for 00 UTC and the lowest monthly average temperature at 30 hPa (for 00 UTC) were breaking records in April. 4) Total ozone over Syowa Station was frequently less than 220 m atm-cm, which was used as a baseline value to ...